2007
DOI: 10.1007/s11151-007-9131-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Sharing, the Cost of Equity and the Optimal Capital Structure of the Regulated Firm

Abstract: This paper considers the relationship between the regulator’s pricing decision and the allocation of risk between consumers and shareholders. Consumers are willing to trade-off price variations against a lower expected price. Prices are higher in adverse economic conditions, but shareholder returns are not necessarily lower. It might be optimal to insure shareholders against market risk, so that consumers could thereby achieve a lower expected price. The allocation of risk between consumers and shareholders de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Stones (2007) demonstrated that the allocation of market risk between consumers and shareholders is influenced by the capital structure of the regulated firm. His model embodies the Lagrangian method and a standard von NeumannÀMorgenstern function of the consumers' utility in income.…”
Section: Previous Studies On Sharingmentioning
confidence: 99%
“…Stones (2007) demonstrated that the allocation of market risk between consumers and shareholders is influenced by the capital structure of the regulated firm. His model embodies the Lagrangian method and a standard von NeumannÀMorgenstern function of the consumers' utility in income.…”
Section: Previous Studies On Sharingmentioning
confidence: 99%
“…7 A literatura aqui apresentada foca no uso estratégico da alavancagem pela firma regulada. Há ainda outra linha de pesquisa, não explorada neste artigo, que foca na definição da alavancagem das firmas reguladas por parte do regulador para maximizar o bem-estar (ver De Fraja eStones, 2004;Stones, 2007).…”
unclassified
“…Our approach differs from De Fraja and Stones () and Stones () where the regulator, rather than the firm, chooses the capital structure of the firm. These papers also assume that the regulator must set p to ensure that the firm never goes bankrupt and shareholders earn their required rate of return.…”
mentioning
confidence: 99%